PENGARUH MOTIVASI KERJA DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASIONAL - Suputra, I Dewa Nyoman Sidan Ari; Sriathi, A.A. Ayu (E-Jurnal Manajemen, 2018)
The development of tourism business requires entrepreneurs to survive any kind of competition and changes that will occur and the need for human resources in order to achieve corporate goals. The main factor in the success of an organization is human resources (HR). The purpose of this study is to analyze the effect of work motivation and job satisfaction on organizational commitment. Objects in this study are work motivation, job satisfaction and organizational commitment. The research was conducted at The Kirana Hotel and Spa Canggu Bali. The population in this research is 45 employees with sampling using Sample saturated method. The data were collected by observation, interview and questionnaire. Analyzer used is multiple linear regression. The result of this research is work motivation have positive and significant effect to organizational commitment, job satisfaction has positive and significant influence to organizational commitment. It needs to be concluded that corporate leaders need to retain employees so that employees are emotionally attached and work on the organization is now the best opportunity.   Keywords : work motivation, job satisfaction, organizational commitment